ETHICS AND DIGITAL PIRACY AMONG MILLENIALS IN EMERGING MARKET - Rizky, Renno Akbarul B1024151006 (Jurnal Manajemen Update, 2019)
ETHICS AND DIGITAL PIRACY AMONG MILLENNIALS IN PONTIANAK By : Renno Akbarul RizkyABSTRACTThe purpose of this paper is to investigate the impact of Millenials?s ethics on their attitude toward digital piracy and intention to use genuine product. The rapid development of file sharing software has greatly increased the ease at which individuals can access digital products, supported by high-speed and affordable internet connection making the internet a refuge for any non-responsible individual doing digital piracy. This research is a survey research that is conducted to understand the causal relationships between variables with the use of questionnaire as the instrument to obtain data. The questionnaire is distributed to 100 sample who fulfill the requirements. The sample of this research is Millenials in Pontianak who are between 19 - 39 years old. In this research, the data analysis method used is Structural Equation Model Partial Least Square (SEMPLS) method. To conduct analysis using PLS method, this research is using smartPLS 3.0 software. The hypothesis of the research is H1 :The risk that consumer perceived of using pirated product have effect to attitude of consumer toward digital piracy, H2: The level of ethics that consumer possesses have effect to attitude of consumer toward digital piracy, H3: The risk that consumer perceived of using pirated product have effect to intention of consumer to use genuine product, H4: The level of ethics that consumer possesses have effect to consumer intention to use genuine product, H5: The consumer attitude toward digital piracy have effect to consumer intention to use genuine product. The result of this research shows that H1, H2, H4 and H5 are accepted but H3 is rejected. Keyword : Morality, Digital piracy, Ethics, MillenialsREFERENCE Ajzen, I. (1991). The theory of planned behavior. Organization Behavior and Human Decision Processes, Vol. 50 No. 2, 179-211.Aleassa, H., Pearson, J. M., & McClurg, S. (2011). Investigating software piracy in Jordan: an extension of the theory of reasoned action. Journal of Business Ethics, Vol. 98 No. 4, 663-676.Allmon, D. E., Page, D., & Roberts, R. (2000). Determinants of perceptions of cheating: ethical orientation, personality and demographics. Journal of Business Ethics, Vol. 23 No. 4, 411-422.Ang, S. H., Cheng, P. S., Lim, E. A., & Tambyah, S. K. (2001). Spot the difference: consumer responses towards counterfeits. Journal of Consumer Marketing, Vol. 18 No. 3, 219-235.Arli, D., Tjiptono, F., & Porto, R. (2015). The impact of moral equity, relativism and attitude on individuals? digital piracy behaviour in a developing country. Marketing Intelligence and Planning, Vol. 33 No. 3, 348-365.Ayers, M. (2006). Cybersounds: Essays on Virtual Music Culture. New York, NY: Peter Lang.Balestrino, A. (2008). It is a theft but not a crime. European Journal of Political Economy, Vol. 24 No. 2, 455-469.Barnett, T., Bass, K., & Brown, G. (1996). Religiosity, ethical ideology, and intentions to report a peer?s wrongdoing. Journal of Business Ethics, Vol. 15 No. 11, 1161-1174.Bateman, C. R., & Valentine, S. R. (2010). Investigating the effects of gender on consumers? moral philosophies and ethical intentions. Journal of Business Ethics, Vol. 95, 393-414.Bauer, R. A. (1960). Consumer Behavior on Risk Taking, Dynamic Marketing for a Changing World. Proceeding of The 43rd Conference of The American Marketing Asociation, 389-398.Blythe, J. (2008). Consumer behaviour. London: Thomson Learning.Bucic, T., Harris, J., & Arli, D. (2012). Ethical consumers among the millennials: a cross-national study. Journal of Business Ethics, Vol. 110 No. 1, 113-131.Champbell, M. C., & Goodstein, R. C. (2001). The Moderating Effect of Perceived Risk on Consumers? Evaluations of Product Incongruity: Preference for the Norm. The Journal of Consumer Research 28(3), 439? 449.Chiou, Huang, J. S., & Lee, H. (2005). The antecedents of music piracy attitudes and Chiou, J., Huang, C., & Lee, H. (Vol. 57 No. 2). ?The antecedents of music piracy attitudes and intentions?. Journal of Business Ethics, 161-174.Cockrill, A., & Goode, M. M. (2012). DVD pirating intentions: angels, devils, chancers and receivers. Journal of Consumer Behaviour Vol. 11 No. 1, 1-10.Coleman, E. (2010). Ethnographic approaches to digital media. Annual Review of Anthropology, Vol. 39 No. 1, 487-505.Conroy, S. J., & Emerson, T. L. (2004). Business ethics and religion:religiosity as a predictor of ethical awareness among students. Journal of Business Ethics, Vol. 50 No. 4, 383-396.Cronan, T. P., & Al-Rafee, S. (2008). Factors that influence the intention to pirate software and media. Journal of Business Ethics, Vol. 78 No. 4, 527-545.Dafler, F. (2013, April 23). Terindah. Retrieved from Memahami dan Mempelajari SmartPLS: http://feroniadafler.blogspot.co.id/2013/04/mempelajari-dan-memahami-smartpls.htmlEl-Bassiouny, N., Taher, A., & Abou-Aish , E. (2011). An empirical assessment of the relationship between character/ethics education and consumer behavior at the tweens segment: the case of Egypt. Young Consumers, Vol. 12 No. 2, 159-170.Fam, K. S., Waller, D. S., & Erdogan , B. Z. (2004). The in?uence of religion on attitudes towards the advertising of controversial products. European Journal of Marketing, Vol. 38 Nos 5/6, 537-555.Fishbein, M., & Ajzen, I. (1975). Belief, attitude, intention, and behavior: An introduction to theory and research. New York: Addison-Wesley Publishing Company, Inc.Geyer, A. L., & Baumeister, R. F. (2005). Religion, morality, and self-control: values, virtues, and vices. In R. F. Paloutzian, & C. L. Park, Handbook of the Psychology of Religion and Spirituality. New York, NY: Guilford Press.Goles, T., Jayatilaka, B., George, B., Parsons, L., Chambers, V., Taylor, D., & Brune, R. (2008). Softlifting: exploring determinants of attitude. Journal of Business Ethics, Vol. 77 No. 4, 481-499.Gunter, W. (2011). ?Criminological predictors of digital piracy: a path analysis?. in Jaishankar, K. (Ed.), Cyber Criminology: Exploring Internet Crimes and Criminal Behavior, CRC Press, Boca Raton, FL,, 173-191.Havlena, W. J., & DeSarbo, W. S. (1991). On the Measurement of Perceived Consumer Risk?, Decision Sciences 22(4). 927?939.Heffner, C. L. (2016). Test Validity and Reliability. Retrieved from AllPsych: http://allpsych.com/researchmethods/validityreliability/Hennig-Thurau, T., Henning, V., & Sattler, H. (2007). ?Consumer ?le sharing of motion pictures?. Journal of Marketing Vol. 71 No. 4, 1-18.Henry. (2011, August 24). Path Analysis with LISREL (Chapter 1). Retrieved from Teori Online: https://teorionline.wordpress.com/2011/08/24/path-analysis-with-lisrel-chapter-1/Hox, J. J., & Bechger, T. (2011). An Introduction to Structural Equation Modeling. Family Science Review, 354-373.Husted, B. W. (2000). The impact of national culture on software piracy. Journal of Business Ethics, Vol. 26 No. 3, 197-211.Jackman, M., & Lorde, T. (2014). Why buy when we can pirate? The role of intentions and willingness to pay in predicting piracy behavior. International Journal of Social Economics, Vol. 41 No. 9, 801-819.Johnson, B. R., Jang, S. J., Larson, D. B., & De Li, S. (2001). Does adolescent religious commitment matter? A reexamination of the effects of religiosity on delinquency. Journal of Research in Crime and Delinquency, Vol. 38 No. 1, 22-44.Johnson, T. (2013). ?NBCU-backed study: online piracy continues to rise dramatically?.Kirkpatrick, L., & Hood, R. (1990). Intrinsic-extrinsic religious orientation: the boon or bane of contemporary psychology of religion? Journal for the Scienti?c Study of Religion, Vol. 29 No. 4, 442-462.Komariah, A., & Satori, D. (2010). Metodologi Penelitian Kualitatif. Bandung: Alfabeta.Kwong, T., & Lee, M. (2002). Behavioral intention model for the exchange mode internet music piracy. Proceedings of the 35thHawaii International Conferenceon System Science, 156-160.Leedy, P. D., & Ormrod, J. E. (2001). Practical Research: Planning and Design. London: Pearson.Light, D., Keller, S., & Calhoun, C. (1989). Sociology. New York, NY: Alfred A. Knopf.Limayem, M., Khalifa, M., & Chin, W. W. (2004). Factors motivating software piracy: a longitudinal study. IEEE Transactions on Engineering Management, Vol. 51 No. 4, 414-425.Limayem, M., Khalifa, M., & Chin, W. W. (2004). Factors Motivating Software Piracy: A Longitudinal Study?. IEEE Transactions on Engineering Management 51(1), 414?425.Lysonski, S., & Durvasula, S. (2008). Digital piracy of MP3s: consumer and ethical predispositions. Journal of Consumer Marketing, Vol. 25 No. 3, 167-178.McCourt, T., & Burkart, P. (2003). When creators, corporations and consumers collide: Napster and the development of on-line music distribution. Media, Culture and Society, Vol. 25 No. 3, 333-350.McDaniel, S. W., & Burnett, J. J. (1990). Consumer religiosity and retail store evaluative criteria. Journal of the Academy of Marketing Science, Vol. 18 No. 2, 101-112.Merriam-Webster. (2018). Merriam-Webster: Questionnaire. Retrieved from Merriam-Webster:: https://www.merriam-webster.com/dictionary/questionnaireMitchell, V. W. (1999). Consumer Perceived Risk: Conceptualisations and Models. European Journal of Marketing 33(1/2), 163?195.Mohamed, N., Shahriza Abdul Karim, N., & Hussein, R. (2012). Computer use ethics among university students and staffs: the in?uence of gender, religious work value and organizational level. Campus-Wide Information Systems, Vol. 29 No. 5, 328-343.Moores, T. T., Nill, A., & Rothenberger, M. (2009). Knowledge of software piracy as an antecedent to reducing pirating behavior. Journal of Computer Information Systems, Vol. 50 No. 1, 82-89.Muncy, J. A., & Vitell, S. J. (1992). Consumer ethics: An investigation of the ethical beliefs of the final consumer. Journal of Business Research, Vol. 24, 297?311.O?Reilly, D., Larsen, G., & Kubacki, K. (2003). Music, Markets and Consumption. Goodfellow Publishers: Oxford.Peace, A. G., Galletta, D. F., & Thong, J. (2003). Software Piracy in the Workplace: A Model and Empirical Test. Journal of Management Information Systems 20(1), 153?177.Peace, A. G., Galletta, D. F., & Thong, J. L. (2003). Software piracy in the workplace: a model and empirical test. Journal of Management Information System, Vol. 20 No. 1, 153-177.Phau, I., & Liang, J. (2012). Downloading digital video games: predictors, moderators and consequences. Marketing Intelligence & Planning, Vol. 30 No. 7, 740-756.Phau, I., & Ng, J. (2010). Predictors of usage intentions of pirated software. Journal of Business Ethics, Vol. 94 No. 1, 23-37.Putra, A. K., Nyoto, R. D., & Pratiwi, H. S. (2017). Rancang Bangun Aplikasi Marketplace Penyedia Jasa Les Private di Kota Pontianak Berbasis Web. Jurnal Sistem dan Teknologi Informasi.Richsen, H. (2015). Validity. Retrieved from Linguistic: http://linguistics.byu.edu/faculty/henrichsenl/ResearchMethods/RM_2_18.htmlRidwan. (2004). Metode dan Teknik Menyusun Tesis. Bandung: Alfabeta.Rojek, C. (2005). P2P leisure exchange: net banditry and the policing of intellectual property. Leisure Studies, Vol. 24 No. 4, 357-369.Sapp, G. L., & Jones, L. (1986). Religious orientation and moral judgment. Journal for the Scienti?c Study of Religion, Vol. 25 No. 2, 208-214.Saroglou, V., Corneille, O., & Van Cappellen, P. (2009). Speak, Lord, your servant is listening?: religious priming activates submissive thoughts and behaviors. International Journal for the Psychology of Religion, Vol. 19 No. 3, 143-154.Schiffman, L. G., Kanuk, L. L., & Wisenblit, J. (2010). Consumer behavior (10th ed.). New Jersey: Pearson Education, Inc.Shields, P., & Rangarajan, N. (2013). A Playbook for Research Methods: Integrating Conceptual Frameworks and Project Management. New Forums Press.Shoham, A., Ruvio , A., & Davidow, M. (2008). (un)Ethical consumer behavior: Robin hoods or plain hoods? Journal of Consumer Marketing, Vol. 25 No. 4, 200-210.Simpson, P. M., Banerjee, D., & Simpson Jr., C. L. (1994). Softlifting: a model of motivating factors. Journal of Business Ethics, Vol. 13 No. 6, 431-438.Sinha, R. K., Machado, F. S., & Sellman, C. (2010). Don?t think twice, it?s all right: music piracy and pricing in a DRM-free environment. Journal of Marketing, Vol. 74, 40-54.Sirkeci, I., & Magnusdottir, L. B. (2011). Understanding illegal music downloading in the UK: a multi-attribute model. Journal of Research in Interactive Marketing, Vol. 5 No. 1, 90-110.Smith, C., & Denton, M. L. (2005). Soul Searching: The Religious and Spiritual Lives of American Teenagers. New York, NY: Oxford University Press.Solomon, S. L., & O?Brien, J. A. (1990). The effect of demographic factors on attitudes toward software piracy. Journal of Computer Information Systems, Vol. 30 No. 3, 41-6.Tan, B. (2002). Understanding Consumer Ethical Decision Making with Respect to Purchase of Pirated Software. Journal of Consumer Marketing 19(2), 96-111.Taylor, G. S., & Shim, J. P. (1993). A comparative examination of attitudes toward software piracy among business professors and executives. Human Relations, Vol. 46 No. 4, 419-33.Taylor, S., Ishida, C., & Wallace, D. (2009). Intention to engage in digital piracy: a conceptual model and empirical test. Journal of Service Research, Vol. 11 No. 3, 246-262.Terpstra, D. E., Rozell, E. J., & Robinson, R. K. (1993). The influence of personality and demographic variables on ethical decisions related to insider trading. The Journal of Psychology, Vol. 127 No. 4, 375-389.Tonoyan, A., & McDaniel, C. (2010). Notes on church and state affairs. Journal of Church & State, Vol. 52 No. 4, 759-765.Van Meter, R. A., Grisaffe, D. B., Chonko, L. B., & Roberts, J. A. (2013). Generation Y?s ethical ideology and its potential workplace implications. Journal of Business Ethics, Vol. 117 No. 1, 93-109.Vitell, S. J., & Paolillo, J. G. (2003). Consumer ethics: the role of religiosity. Journal of Business Ethics, Vol. 46 No. 2, 151-162.Vitell, S. J., Ramos, E., & Nishihara, C. M. (2010). The role of ethics and social responsibility in organizationalsuccess:aSpanishperspective. Journal of Business Ethics, Vol. 91 No. 4, 467-483.Wardani, P. (2012). Faktor-faktor yang Mempengaruhi Luas Pengungkapan Sukarela. Surabaya: Fakultas Bisnis Universitas Katolik Widya Mandala.Waters, R. D., & Bortree, D. S. (2012). Can we talk about the direction of this church? The impact of responsiveness and con?ict on millennials? relationship with religious institutions. Journal of Media and Religion, Vol. 11 No. 4, 200-215.West, J. (1995). Software right and Japan?s shift to an information society. Asian Survey, Vol. 35 No. 12, 1118-39.White, R. (2014). Australian online piracy on the ris. www.craveonline.com.au/music/ tech-and-gadgets-news/775249-australian-online-piracy-rise .Wilkes, R., Burnett, J., & Howell, R. D. (1986). On the Meaning and Measurement of Religiosity in Consumer Research. Journal of the Academy of Marketing Science (14), 47-56.Williams, C. (2007). Research Methods. Journal of Business & Economics Research.Yang, D., & Sonmez, M. (2007). Economic and cultural impact on intellectual property violations: a study of software piracy. Journal of World Trade, Vol. 41 No. 4, 731-750.Yoon, C. (2011). Theory of planned behavior and ethics theory in digital piracy: an integrated model. Journal of Business Ethics, Vol. 100 No. 3, 405-417.Yu, S. (2012). College students? justi?cation for digital piracy: a mixed methods study. Journal of Mixed Methods Research, Vol. 6 No. 4, 364-378.